The Mobile Phones Consumers Protection - Luiela, Csorba; Florin, Isac; Radu, Cureteanu; Sergiu, Rusu (Richtmann Publishing, 2012)
This paper analyzes the issue of promoting the interests of mobile consumers, from two perspectives. Thefirst is designed to evaluate and highlight the awareness, knowledge and education of the Romanianconsumers regarding the impact of the mobile phone use on the health and body integrity, and the secondanalyzes the behavior which the same consumer takes in environmental problems that the use ofconventional mobiles may generate.For a pertinent analysis, a survey questionnaire was developed, thatincludes three sections. The first consists of questions that test consumer awareness about the impact thatmobile phone has on their health. Sections two and three examine the ecological behavior of mobilephones consumers.